MANAGEMENT OF GESTATIONAL HYPERTENSION THROUGH FAMILY MEDICINE APPROACH: CASE REPORT - Ayu Pratiwi, Silvi; Ernawati (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
Several factors contribute to the incidence of hypertension during pregnancy, including a familial history of hypertension, obesity, and unhealthy dietary habits. Family habits can have a substantial impact on lifestyle, especially nutritional choices. This report presents a case of gestational hypertension in Mrs. DK, a 20-year-old pregnant woman with obesity, who was managed utilizing a family medicine approach. The identified root cause of her problem as an inherited genetic susceptibility to hypertension, exacerbated by poor dietary habit within the family. Mrs. DK and her family was given comprehensive intervention to ensure a healthy pregnancy. This strategy provided her with results in the form of controlled blood pressure and enhanced understanding of her condition and nutritional requirements, as well as strategies to fulfill them. Ongoing surveillance is necessary to guarantee that goals are being met.